A promising new approach to cancer therapy: Targeting iron metabolism in cancer stem cells. (December 2018) - El Hout, Mouradi; Dos Santos, Leïla; Hamaï, Ahmed; Mehrpour, Maryam
Abstract: Iron is an essential nutrient that facilitates cell proliferation and growth. Iron can be detrimental, however. The ability of iron to cycle between oxidized and reduced forms contributes to the formation of free radicals. An excess of free radicals leads to lipid peroxidation, more reactive oxygen species and oxidative stress, damage to DNA and other biomolecules, and, if potentially, tumorigenesis. Iron also has a role in the maintenance of the tumor microenvironment and in metastasis. Pathways of iron acquisition, efflux, storage, and regulation are all perturbed in cancer, suggesting that reprogramming of iron metabolism is a central aspect of tumor cell survival. Recent studies have shed light on the role of iron metabolism in cancer stem cells (CSC) and suggest that specific targeting of iron metabolism in CSCs may improve the efficacy of cancer therapy. In this review, we first summarize briefly our current understanding of the intracellular processes involving iron, the effect of dietary iron, and its relation to cancer. We emphasize the importance of modifier "iron genes" in cancer and the possibility that these genes may encode biomarkers that may be used clinically. We then provide an update on the role of iron in metabolic reprogramming, the epithelial-mesenchymal transition, and the regulation of epigenetic marks essential for CSC maintenance and plasticity. Finally, we discuss the potential of targeting a recently discovered form of iron-regulated cell death, ferroptosis, in CSCs for treatment of cancer.